Perceived Value Of Mobile Payment Apps: A Literature Review (Journal of Namibian Studies : History Politics Culture, 2023)
Mobile wallet is a natural advance step in the development of payment methods. It is an opportunity for financial growth and is becoming a common tool for carrying out various financial transactions. It can support several transactions including consumer to consumer, consumer to business, consumer to machine, and consumer to online. The widespread penetration of mobile payment systems could drastically change the methods in which consumers purchase goods and services. The main objective of this research is to build antecedents and outcomes of perceived value in the context of using mobile payment apps. To accomplish this objective, the researcher surveyed around 50 literatures with reference to the utility of mobile payment apps. From the study it was revealed that ease of use, convenience, anytime and anywhere was the common associated value by the users with mobile payment apps.